2019
DOI: 10.1016/j.immuni.2019.01.008
|View full text |Cite
|
Sign up to set email alerts
|

A Macrophage-Pericyte Axis Directs Tissue Restoration via Amphiregulin-Induced Transforming Growth Factor Beta Activation

Abstract: Summary The epidermal growth factor receptor ligand Amphiregulin has a well-documented role in the restoration of tissue homeostasis after injury; however, the mechanism by which Amphiregulin contributes to wound repair remains unknown. Here we show that Amphiregulin functioned by releasing bioactive transforming growth factor beta (TGF-β) from latent complexes via integrin-α V activation. Using acute injury models in two different tissues, we found that by inducing TGF-β acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
133
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(142 citation statements)
references
References 53 publications
5
133
0
4
Order By: Relevance
“…Although Areg is increasingly recognized to play a role in airway injury, repair, and fibrosis, its contribution to CLAD in human lung transplant recipients had not been previously characterized. In this study, we analyzed two independent cohorts of lung recipients to demonstrate that Areg protein is increased in the BAL in association with CLAD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Areg is increasingly recognized to play a role in airway injury, repair, and fibrosis, its contribution to CLAD in human lung transplant recipients had not been previously characterized. In this study, we analyzed two independent cohorts of lung recipients to demonstrate that Areg protein is increased in the BAL in association with CLAD.…”
Section: Discussionmentioning
confidence: 99%
“…Current data suggest that Areg can be expressed by multiple populations of activated immune cells and can also influence immune cell function . Moreover, a recent study by Minutti et al in an experimental lung injury model demonstrated that Areg secreted by tissue‐resident immune cells is critical to regulating local concentrations of activated transforming growth factor beta (TGF‐β), a key fibrotic mediator. Thus, suggesting a potential link between EGFR signaling and TGF‐β‐mediated fibrosis in chronic inflammatory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…We recently found that one critical function of Amphiregulin is to locally activate latent TGF β . Thus, via this local release of TGF β , Amphiregulin may contribute to both the local suppression of inflammation as well as to the local differentiation of tissue stem cells, and in this way to the process of wound healing and restoration of tissue homeostasis.…”
Section: The Role Of Amphiregulin In Immune Regulation and Wound Healmentioning
confidence: 99%
“…In particular, the local activation of the transforming growth factor‐beta (TGFβ) induces the differentiation of pericytes into myofibroblasts during the development of tissue fibrosis . The epidermal growth factor (EGF) like growth factor amphiregulin has recently been identified as being a critical factor that induces this local activation of TGFβ on pericytes and thus their differentiation into myofibroblasts . Amphiregulin is a cytokine, involved in immunity against helminth infection, in immune regulation, and in wound repair .…”
mentioning
confidence: 99%
“…The EGFR shows a so‐called “agonistic bias,” which means that ligands with different affinities induce the activation of different downstream signaling pathways (Figure ). Consequently, the low affinity‐ligand amphiregulin induces the activation of TGFβ, whereas the high‐affinity ligand HB‐EGF activates the intracellular inhibitor of TGFβ‐signaling TGIF; in this way preventing the differentiation of pericytes into myofibroblasts . As a consequence, Hbegf ‐/‐ mice develop more severe forms of tissue fibrosis .…”
mentioning
confidence: 99%